Social and Non-Social Cognitive Enhancement in Cocaine Users—A Closer Look on Enhancement Motives for Cocaine Consumption - Kexel, Ann-Kathrin; Vonmoos, Matthias; Preller, Katrin H.; Hulka, Lea M.; Seifritz, Erich; Quednow, Boris B. (Frontiers in Psychiatry, 2020)
Background: Cognitive disturbances of chronic cocaine users (CU) have been repeatedly investigated. However, it is yet unknown how CU using cocaine for cognitive or social enhancement differ from stimulant-naïve controls and CU that do not have these motives. More precisely, we assumed that CU with an enhancement motive self-medicate deficits in specific cognitive abilities, i.e., they use cocaine to enhance their performance in either social (social motive) or non-social cognitive situations (cognitive motive). Methods: Forty-two CU were categorized according to their motives for cocaine consumption into social and non-social motive groups as well as cognitive and non-cognitive motive groups, respectively. Subsequently, CU motive groups were compared to 48 stimulant-naïve controls in their social and non-social cognitive functioning applying a comprehensive neuropsychological test battery. Results: The social motive group showed deficits in cognitive empathy compared to controls (Cohen’s d=0.65) and the non-social motive group (d=0.60). No mentionable effects were found for emotional empathy and Theory-of-Mind. Cognitive and non-cognitive motive groups both showed general cognitive deficits but with different patterns of impairments compared to controls: the cognitive motive group had deficits mainly in working memory (d=0.84) and declarative memory (d=0.60), whereas the non-cognitive motive group also had deficits in working memory (d=0.61) but additionally in executive functions (d=0.67). For the domains declarative memory and executive functions, the respective other CU group displayed intermediate performance. Conclusions: This study demonstrates that cocaine is partially instrumentalized by CU with specific enhancement motives to counteract related cognitive impairments.